Stained glass work, Archangel Gabriel - Ghosh, Ayan (2023)
Stained glass panel with winged figure of the Archangel Gabriel carrying lilies. Gabriel is mentioned in the Hebrew Bible, the New Testament, and the Quran. Many Christian traditions – including Catholicism, Eastern Orthodoxy, Lutheranism, and Anglicanism — revere Gabriel as a saint.